Structural characterization of in‐situ silicided contacts textured on p‐type [001] silicon. Issue 1 (25th November 2013) - Badalà, Paolo; Faro, Giuseppe; Marcellino, Cinzia; Pellegrino, Giovanna; Santangelo, Antonello; Alberti, Alessandra; Cristiano, Fuccio; Pichler, Peter; Tavernier, Clément; Windl, Wolfgang
Abstract Nickel silicide is widely used to realize contact terminals of integrated circuits and is usually formed by ex‐situ heating treatments. In‐situ reactions during sputter deposition of a Ni layer onto a HF p‐type [001] Si substrate have been investigated in this work, by means of transmission electron microscopy, X‐ray diffraction and X‐ray reflectivity analyses. A thin layer of polycrystalline silicide, with extremely flat interfaces and in fiber texture with the Si substrate, has been obtained by introducing a sputter etching step just before Ni deposition and properly modulating its duration. The work has also been aimed to decouple the thermal impact of sputter etching from its effect on surface cleaning, disclosing its key role in the whole reaction process. (© 2014 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)